2013
DOI: 10.1080/10934529.2014.854674
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hygiene and localised treatment on the quality of drinking water in Masaka, Rwanda

Abstract: The worldwide prevalence of waterborne diseases has been attributed to the lack of safe water, inadequate sanitation and hygiene. This study evaluated socio-demographic factors, microbiological quality of water at source and point of use (POU) at households, water handling and sanitation practices in a rural Rwandan community. Thirty five water samples from the source, Nyabarongo River, and water at point of use (POU) treated with the Slow Sand Filter (SSF) and Sûr'Eau methods, were analysed for total coliform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
14
2
Order By: Relevance
“…The findings of this study contrast greatly with those of Uwimphuwe et al [18], in their study in Rwanda that showed 67% of the respondents treated their water. This study was comparable to other studies by Onyango and Angienda [5] in Western Kenya found out domestic water treatment practices to include boiling and use of sodium hypochlorite.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study contrast greatly with those of Uwimphuwe et al [18], in their study in Rwanda that showed 67% of the respondents treated their water. This study was comparable to other studies by Onyango and Angienda [5] in Western Kenya found out domestic water treatment practices to include boiling and use of sodium hypochlorite.…”
Section: Discussioncontrasting
confidence: 99%
“…This lack of basic hand washing hygiene adversely affects household water quality as the household members dip their hands in storage containers to access water for household tasks. This study finding contrasted greatly to observations made by Uwimphuwe et al [18] in their study in Masaka Rwanda, in which they found that 97% of the respondents washed their hands before eating and 20% of the respondents washed their hands before preparing food and 31% of the respondents washed their hands after handling babies. The hand-washing practice is poorly observed in the study area.…”
Section: Discussioncontrasting
confidence: 97%
“…The water quality in Rwanda is being exposed to several degrading and polluting forces being natural and manmade. Previous reports on the water physico-chemical parameters and heavy metals Usanzineza et al, 2011;Mupenzi et al, 2009;Muhirwa et al, 2010;Uwimpuhwe et al, 2014) estimated low pH level 5.9 at the Nyabugogo River compared to the standards of the World Health Organization and European Union (pH 6.0-8.0). Moreover, the total suspended solids of the Rweru-Mugesera wetland, Congo and Nile basins (Rwandan side), 67.91, 920.90 and 162.86 mg/l, respectively, were above the standards (˂30 mg/l).…”
Section: Trends In Water Quality In Rwandamentioning
confidence: 93%
“…The assessment on microbiological water quality in Kigali city, the capital of Rwanda (Table 3) revealed the presence of Klebsiella, Enterobacter, Staphylococcus and Escherichia coli in river water and ground water (Uwimpuhwe et al, 2014;Rutanga, 2014;Nigatu et al, 2015). Although the drinking water seems polluted, the Government of Rwanda through her Ministry of health recommends citizens to drink boiled water and use of Sûr'Eau (water purification product, commonly used in Rwanda) in order to minimize the pollution resulting risks from the water being consumed.…”
Section: Trends In Water Quality In Rwandamentioning
confidence: 99%
“…At the time of the audit (April 2016), 3 pits were already full and they were digging a fourth one. These pits are located on the top of the hill and if it rains heavily, they are likely to overflow and spread into the neighborhood and contaminate water and crops [3][4][5][6]. This leads to spread of disease to the neighboring population.…”
Section: Inappropriate Solid and Liquid Waste Disposalmentioning
confidence: 99%